Trends and Perspectives: Survey to Graduates from the Licentiate Degree in Pedagogy with an Emphasis on Teaching from Universidad Nacional - Azofeifa Lizano, Ana (2024)
In 2023, the committee of the permanent activity of Self-Assessment and Quality Management of the Department of Educology (APAGCDE in Spanish) carried out a survey with the graduated population of the Licentiate Degree of Pedagogy with am Emphasis on Teaching (LPED in Spanish) of Universidad Nacional, with the purpose of analyzing their opinions on the main causes that may affect the duration of the final graduation project (TFG in Spanish); obtaining information concerning the job market; identifying areas for updating; and reflecting on the improvements required by the LPED’s curriculum. This document aims to be an-input for strengthening the major, which seeks to provide an offer in accordance with current needs and demands.